Thermogravimetric kinetics and pyrolytic tri-state products analysis towards insights into understanding the pyrolysis mechanism of Spirulina platensis with calcium oxide. (January 2022) - Hu, Mian; Zhang, Haiyang; Ye, Zhiheng; Ma, Jiajia; Chen, Zhihua; Wang, Junliang; Wang, Cheng; Pan, Zhiyan
Abstract: Thermogravimetric kinetics and pyrolytic tri-state products analyses towards insights into understanding the pyrolysis mechanism of Spirulina platensis with calcium oxide were investigated using a thermogravimetric analyzer and a fixed bed reactor, respectively. The pyrolysis kinetics were studied by Friedman method and results indicated that the f ( α )=(1- α ) 4 with A 0  = 1.99E+10s −1 and f ( α ) = − 1 / l n ( 1 − α ) with A 0  = 8.33E+11s −1 were suitable for Spirulina platensis and Spirulina platensis  + CaO (stage II) pyrolysis, respectively. According to pyrolysis behaviors and kinetics analyzed, the potential reaction behaviors of CaO during the pyrolysis of Spirulina platensis were explored. Spirulina platensis pyrolytic tri-state products analyzed indicated that, when CaO as additive, the gas yield markedly increased with more H2, CO content and less CO2 content and the bio-oil yield significantly decreased. Moreover, the contents of aromatic compounds, aliphatic compounds, phenols and ketons obviously increased in bio-oil with the appreciably decreased in the contents of esters, N -containing compounds, O-containing compounds and acids. Based on the evolutionary mechanism of CaO and pyrolytic tri-state products, the pyrolysis mechanism of Spirulina platensis with calcium oxide was proposed. Graphical abstract: Image 1